(untitled) (INNOVATIVE ECONOMY, 2025)
Parkhomets M.K., Uniiat L.M., Chorna N.P., Hradovyi V.V. ORGANIZATIONAL AND ECONOMIC DIRECTIONS OF EFFECTIVE ACTIVITY OF AN AGRICULTURAL ENTERPRISE Purpose. The aim of the article is a retrospective analysis of the achieved level of agricultural production efficiency and substantiation of the directions of effective activity of the divisions of the enterprise PAE (Private agro-industrial enterprise) “Dzvin” for the future. Methodology of research. The theoretical and methodological basis of the study was the basic provisions of economic theory and scientific developments of scientists. The following methods were used in the research process: retrospective analysis of trends in the economic efficiency of crop and livestock production in PAE “Dzvin”; monographic (covering the experience of the best enterprises in Ukraine); statistical and economic (study of the influence of internal and external factors on the efficiency of production and sales of agricultural products); abstract and logical (theoretical generalizations and formation of conclusions, literary sources) and others. Findings. The article highlights the current economic state of the activities of the divisions of the agricultural enterprise, substantiates the organizational and economic directions of their effective activity for the future. Scientific recommendations are developed for the prospective organization of the system of conducting profitable pig farming in enterprises in Ukraine. Optimized rational farms by the number of pig herds: small; medium; large for the country’s enterprises. Originality. Inhibiting factors were identified and recommendations were developed to increase profitability and further effective development of the enterprise’s divisions. The feasibility of building a plant with a capacity of 20-30 thousand tons/year for the production of high-quality biodiesel from rapeseed was proposed, which will contribute to the sustainable economic development of enterprises. Practical value. The proposed scientific and methodological recommendations and practical developments make it possible to form a strategy for further effective development of divisions of both the analysed PAE “Dzvin” and operating enterprises of the country, which is of great importance, especially for the further development of pig farming in the conditions of the post-war period of revival of Ukraine. Key words: divisions of the enterprise, production, cost and price of products, profitability and unprofitability of production, resource-saving technologies, profitability of the division and enterprise.